INTEGRASI TAZKIYATUN NAFS DALAM MENGATASI OVERTHINKING PADA GENERASI Z DI ERA DIGITAL - Mayrina Eka Prasetyo Budi; Astika Dewi Putri Supriyadi (Program Studi Bimbingan dan Konseling Pendidikan Islam, 2026)
Overthinking among Generation Z has become an increasingly prevalent psychological issue in the digital era. The rapid development of technology and intensive use of social media contribute to the emergence of rumination, a repetitive pattern of negative thinking without clear solutions, which leads to anxiety, sleep disturbances, and decreased concentration. This study aims to analyze the integration of tazkiyatun nafs as an approach to overcoming overthinking among Generation Z. This research uses a qualitative approach with a literature study method by examining various relevant scientific sources. The results show that modern psychological approaches, such as mindfulness and cognitive-behavioral techniques, are effective in managing symptoms of overthinking but tend to focus only on cognitive and emotional aspects. In contrast, the concept of tazkiyatun nafs in Islamic psychology offers a more comprehensive approach through spiritual purification, self-control, and strengthening the relationship with God. The integration between rumination and tazkiyatun nafs indicates that spiritual approaches can play a significant role in breaking negative thought cycles. Therefore, tazkiyatun nafs can serve as a preventive and curative strategy in addressing overthinking among Generation Z in the digital era.